A 0D/2D Heterojunction Composite of Polymeric Carbon Nitride and ZIF-8-Derived ZnO for Photocatalytic Organic Pollutant Degradation - Vandana P. Viswanathan; Vaishak T. Balakrishnan; Nayarassery N. Adarsh; Binsy Varghese V; Suresh Mathew (Crystals, 2022)
Solar photocatalytic technology based on semiconducting materials has gained the attention of the scientific community to solve the energy crisis and environmental remediation. Zeolitic imidazolate frameworks (ZIFs) are a subfamily of metal–organic frameworks (MOFs) with the isomorphic topologies of zeolites and coordinative compositions of MOFs. Owing to high specific surface areas, tunable channels and high thermal stabilities, zeolitic imidazolate frameworks (ZIFs) have been used in catalytic applications. In this paper, ZIF-8 was used as a matrix to synthesize 0D/2D heterojunction photocatalysts, viz., ZnO/C3N4-x% (x = 2.5, 5 and 10), for the photocatalytic degradation study of rhodamine B (RhB). The synthesized composite materials were characterized using FTIR, PXRD, UVDRS, PL, TEM, and BET analyses. TEM images showed the nearby contacts between ZnO and C3N4 in the hybrid and the uniform distribution of ZnO on the surface of the C3N4 nanosheet, thus increasing the development of 0D/2D heterojunction. The hybrid system ZnO/C3N4-5% (ZCN-5) showed good photocatalytic activity for the degradation of RhB under sunlight. A possible mechanism for the improved photocatalytic activity of the ZnO/C3N4 composite is also suggested. This exploratory study demonstrates the effective separation and migration of photo-induced electron–hole pairs between the 2D C3N4 sheet and 0D ZnO for the improved performance of heterojunction photocatalysts.